UPAYA PENURUNAN ANGKA STUNTING MELALUI PEMBERIAN MAKANAN TAMBAHAN (PMT) DI DESA SENARU - Kurahman, Taufik; Antoni, Antoni; Ikhsan, Lalu Fatihul; Aunida, Lale Fadilla Putri; Septikyanti, Septikyanti; Noviani, Dina; Ningrum, Berlian Agustin; Rosimarsandi, Baiq Maudina; Nurhaviza, Siti; Rohmi, Baiq Ayu Zahari Al; Sudirman, Sudirman (Universitas Mataram, 2023)
The university engages in community service activities (KKN). In the village of Senaru, Bayan Subdistrict, North Lombok Regency, a group of students carried out various real work activities as part of the program, including the implementation of the Supplementary Feeding Program (SFP) aimed at reducing the incidence of stunting in Senaru Village. Senaru Village has 81 stunted children due to their poor health status. Stunting is a form of malnutrition caused by insufficient food intake over an extended period, resulting in nutritional deficiencies. The objective of this activity is to raise awareness among the community about the importance of nutrition for children and to provide SFP as a tangible measure to reduce the risk of stunting in Senaru Village. This activity was conducted through Focus Group Discussions involving stakeholders in Senaru Village, such as the Mother's Empowerment and Family Welfare Movement (PKK) and the Village Health Team. Additionally, there were awareness campaigns and training sessions for creating various processed SFP menus using eggs. The outcomes of this activity include an increased understanding within the community regarding the significance of nutrition for children and a decrease in the stunting rate, decreasing from an initial 81 stunted children to 71. The reduction in stunting is attributed to the intensive provision of SFP over a span of 31 days. As a result, it is anticipated that this program will contribute to reducing the stunting rate in Senaru Village and ultimately lead to a Stunting-Free Senaru Village. The Supplementary Feeding Program (SFP) has proven effective in decreasing stunting rates among toddlers.